Kelembagaan Tingkat Desa dalam Pemberdayaan Penyandang Disabilitas - Yuhastuti, Fransiska Tri; Supranoto, Supranoto; Makmur, M. Hadi (University of Jember, 2021)
This study aims to describe institutions in the empowerment of people with mild and moderate levels of disabilities in Karangpatihan Village, District of Balong, Ponorogo Regency. Karangpatihan Village is one village that has been labeled as an idiot village due to the existence of a number of persons with disabilities. They live in weak, vulnerable, poor and underdeveloped conditions. Therefore, some participants collaborate based on the rules of the game that are carried out to seek empowerment, so that they are expected to improve the quality of their live. This study attempts to provide a clear description using qualitative approach with descriptive analysis method. Data collection techniques used interview, observation, documentation and literature study. Informants were determined by purposive sampling and snowball sampling, while data validity was verified using persistent observation, triangulation and peer examination through discussion. Data analysis techniques used analysis model from Miles and Huberman which included data collection, data reduction, data presentation and conclusion drawing. The results of this study are the description of values, rules, norms and laws and regulations used, participants involved, mechanisms for changing values, rules and norms, laws and regulations used and activities carried out in efforts to empower people with mild and moderate levels of disabilities in Karangpatihan Village, District of Balong, Ponorogo Regency